Contemporary thought in the Muslim world: trends, themes, and issues - Kersten, Carool (Contemporary thought in the Islamic world, 2019)
Acknowledgements -- Introduction -- 1. The problem of taxonomy: Categorizing contemporary Muslim intellectuals -- 2. Philosophies of knowledge: Transmission and reason -- 3. Scripture: Alternative ways of engaging with the Qur'an -- 4. Spiritual dimensions of contemporary Muslim thought: Sufism today: psychology, literature, and islamization of knowledge -- 5. Islam and politics: Thinking about secularity, freedom, and democracy -- 6. Shari'a: Islamic legal system or ethical guideline? -- 7. Dealing with difference and plurality: Emancipation, toleration, and human rights -- 8. Issues of the twenty-first century: Globalization, ecology, and medical ethics -- Bibliography -- Index.